Evolved gas analysis (TG-DSC-FTIR) and (Pyr-GC-MS) in the disposal of medicines (aceclofenac) - Colman, Maristela Denck; Silveira Lazzarotto, Simone Rosa da; Lazzarotto, Marcelo; Hansel, Fabricio Augusto; Denck Colman, Tiago Andre [UNESP]; Schnitzler, Egon (Elsevier B.V., 2016)
During the twentieth century the growth of industrialisation, urbanisation and populations culminated in huge areas of waste disposal worldwide. Consequently, the management of the disposal of medicines (expired or not) is important in order to minimise the possibility of environmental pollution. A sample of aceclofenac (purity = 99.77% and m.p. = 151.63 degrees C) was analysed by TG-DSC-FTIR in nitrogen atmosphere. The TG-DSC curves showed two main stages of decomposition, with loss of organic matter generating carbonaceous derivatives as final residue. The use of coupled FTIR suggested the loss of CO, CO2 and/or 2-chloro-propanoic acid/2-chloro-butanoic acid. The use of fast pyrolysis (Pyr) coupled with GC-MS suggested that the main compounds that were released were 1-(2,6-dichloropheny1)-2-indolinone and 2,6-dichloro-N-(2-methylphenyl)-benzenamine. The differences in the results between the techniques were due to the experimental conditions used for each instrument. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Pyrolysis; Aceclofenac; Thermal analysis; TG-DSC-FTIR; Pyr-GC-MS